Long-term renal and cardiovascular outcome of living kidney donors: A single-center retrospective observation study - Colucci, Vincenza; Gallo, Pasquale; Simone, Simona; Morrone, Luigi; Alfieri, Carlo Maria; Gesualdo, Loreto; Castellano, Giuseppe (Frontiers in Medicine, 2022)
Background The nephrectomy for donation reduces the renal parenchyma and glomerular filtration rate(GFR). It is important to understand the clinical consequences of kidney donation by a living donor. Methods In this single-centre, observational, retrospective study, we defined the renal and cardiovascular outcomes of living kidney donors. We analysed data of 124-donors who donated at the Kidney Transplant-Center(TC) of Bari between February-2002 and December-2018. Biometric data collected at visit-0, that is, at the time of the study of the donor candidate, and at visit-1, or rather at the last nephrological checkup (October-2018/August-2019) were compared. Results An overall drop in GFR of 29mL/min was observed over the analysed period of 81+/-59mths. At visit-1, 2 donors developed chronic renal failure, including one in ESKD who underwent a kidney transplant. No relationship between age at donation and GFR drop was found. A trend toward an increase in obese people was reported; 28% of patients had compensated dyslipidemia and 35% were treated for hypertension. During the follow-up time, 3% had major cardiovascular events and 24% were lost to follow-up. One patient died. Conclusions The age of the donor doesn’t represent a basic element for reducing GFR or for the occurrence of major cardiovascular events. Furthermore, older donor candidates, in optimal health, should not be excluded from the donation. It is important to promote careful and timely follow-up of the donor, preventing the most common clinical consequences of nephrectomy, in consideration of the poor compliance of a large part of donors over the long-term post donation period.